Spatial-Intelligent Decision Support System for Sustainable Downstream Palm Oil Based Agroindustry within the Supply Chain Network: A Systematic Literature Review and Future Research - Safriyana Safriyana; Marimin Marimin; Elisa Anggraeni; Illah Sailah (International Journal of Supply Chain Management, 2020)
Oil palm plantations as one of the sexiest commodities; produce a high yield of oil and fat that can be used in various sectors. The prospect of oil palm and its derivative products is good, but there are obstacles and problems faced that are mainly related to sustainability issues in oil palm plantations and its downstream process. Therefore, it is important to study the decision-making process that are needed to develop sustainable palm oil agroindustry. This paper aims at providing a comprehensive literature review for decision support system for sustainable agroindustry. Totally, 186 scientific publication articles from 2005 to 2019 were reviewed and synthesized. The reviewed articles were categorize based on the keywords of palm oil sustainability, geographic information system (GIS), and decision support system (DSS). The research gap and pointers for future research that are identified is the lack of sustainability aspect inclusion on decision-making process. We also identified the lack discussion of integrated spatial and intelligent tools through DSS for better, faster, and smarter decision-making process. In the end part of the paper, a pointer for possible future research was develop in terms of combination through spatial-intelligent system applying business analytics for sustainable agroindustry.